Pengaruh Indikator Mekanisme Corporate Governance dan Ukuran Perusahaan terhadap Kinerja Perusahaan pada Perusahaan Manufaktur Periode 2012-2014 - Ayurisa Ristika; Dwi Handayani; Intan Immanuela (Fakultas Bisnis, 2017)
This study aims to prove empirically that the number of board of directors, the proportion of independent board, debt to equity, institutional ownership, and firm size affect the performance of companies in the manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. Sampling was done by purposive sampling and obtained a sample of 195 companies listed in the Indonesia Stock Exchange. The hypothesis test uses multiple linear regression analysis with SPSS version 17. The results of this study prove that a variable institutional ownership and firm size has positive eeffect on the company performance. The results of this study also prove that the proportion of independent board variables negative effect on the company performance. While variable number of the board of directors and the debt to equity has no effect on the company performance.